Modeling the mechanical response of gas hydrate reservoirs in triaxial stress space. (8th October 2019) - Wu, Yang; Li, Neng; Hyodo, Masayuki; Gu, Meixiang; Cui, Jie; Spencer, Billie F.
Abstract: Exploitation of gas from deep-sea methane hydrate-bearing layers might lead to some geological disasters, including marine landslides and excessive settlement of marine ground. The first offshore gas production tests for methane hydrate-bearing sediments were carried out in eastern Nankai Trough. However, knowledge on mechanical behavior of gas hydrate reservoirs with similar gradation and minerology component to the marine sediment is still insufficient. Consequently, proper modeling of geomechanical properties of methane hydrate-bearing sediments is crucial for reservoir simulation and deep ocean ground stability analysis for long-term gas production in the future. This study conducted a series of triaxial shear tests to examine the shear response of methane hydrate-bearing sediments with a similar grading curve and minerology components to the hydrate-rich sediments in Nankai Trough. The test results demonstrated that the presence of hydrate mass between sand grains altered the stress-strain pattern from strain-hardening to postpeak strain-softening. A simple constitutive model based on several empirical relationships of granular materials is proposed to describe the stress-strain relationship of methane hydrate-bearing sediments under triaxial stress condition. This model can reproduce the enhancement of shear strength, initial stiffness, and dilation behavior of methane hydrate-bearing sediments containing different amounts of fines content with a rise in the methane hydrate saturation at a wide range of effective confining pressures. The numerical results indicate that the parameter A associated with initial stiffness of stress-strain curve and the parameter α related with dilation properties are jointly governed by the confining pressure, fines content, and hydrate saturation. Highlights: A simple constitutive model is proposed to capture the mechanical properties of methane hydrate-bearing sediment. The influence of hydrate saturation on the stress-dilatancy relationship is included. Mean stress at the critical state is an influential parameter governing stress-strain pattern. The effect of the presence of hydrate on the peak shear strength, initial stiffness and dilation behavior is simulated.